2014
DOI: 10.1021/jp506509c
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characteristics of Cholera Toxin and Escherichia coli Heat-Labile Enterotoxin Structure and Chemistry Lead to Differential Toxicity

Abstract: The biophysical chemistry of macromolecular complexes confer their functional characteristics. We investigate the mechanisms that make the AB5 holotoxin of Vibrio cholerae (CT) a significantly more pathogenic molecule than the enterotoxin of Escherichia coli (LT) with which it shares 88% similarity and whose structure is homologous with a backbone RMSD of 0.84 Å and imposes its deleterious effects though the same process to constitutively ADP-ribosylate adenylate cyclase. We present computational data that cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…Ceftazidime was docked (Autodock Vina 1.1.2) ( 34 , 35 ) onto the Syk tandem SH2 domains (PDB 4FL2) ( 36 ). Cluster analysis indicated several possible binding sites for ceftazadime within the tandem SH2 domains of SYK.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceftazidime was docked (Autodock Vina 1.1.2) ( 34 , 35 ) onto the Syk tandem SH2 domains (PDB 4FL2) ( 36 ). Cluster analysis indicated several possible binding sites for ceftazadime within the tandem SH2 domains of SYK.…”
Section: Resultsmentioning
confidence: 99%
“…All docking was done in triplicate for both large and focused search boxes and was initialized with random seeds. Autodock Tools was used to prepare ceftazidime for docking into the input molecular model of SYK, prepared using standard protocols ( 34 , 35 ) from crystallographic structure 4FL2 ( 36 ). Docking was completed with Autodock Vina 1.1.2 ( 37 , 38 ) using an initial unbiased search box ( Supplementary Figure S7 ) with center (−11.6, 3.6, 34.0) Å and size (90,80,80) Å and then refined by using a focused box encompassing the putative binding sites, identified from the first round.…”
Section: Methodsmentioning
confidence: 99%
“…The exact structural basis for this evident difference in detergent resistance was not explored, and it remains unclear if or how the difference in stability manifested as a difference in toxicity. Recent molecular dynamics modeling 38 of the exchanged sequences within a LTI B subunit pentamer suggested that water accessibility and the energetics of binding are very different between A2 domains of the cholera and LTI sequences. It was proposed that the toxicity difference might be due to structural changes around the conserved ER localization signal found on the membrane associating side of the complex.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this, Craft et al . 38 observed in steered MD studies that the electrostatic environment of the histidine significantly reduces the force needed to drive the cholera A2 domain further into the B subunit pore compared to the LTI A2 domain. In our model, disassociation of the cholera A2 domain from the B subunits requires that the histidine side chain be deprotonated, which is restricted both by electrostatic interactions with nearby aspartates and reduced water/proton accessibility in the core of the complex.…”
Section: Discussionmentioning
confidence: 99%
“…The A2 fragment ends in a somewhat disordered segment adopting a small helix, where the pore is widening toward the membrane (Figure 7.2A, insert). This segment is more buried in CT compared to LT, where it extends further through the pore (Figure 7.3), potentially explaining the milder symptoms caused by LT compared to CT [27]: A larger number of interactions of the B pentamer with the CTA2 tail compared to LTA2 rationalizes the increased stability and concomitant increase in toxicity observed for holotoxin chimera featuring the 10-amino-acid-residue-stretch from CT (226)(227)(228)(229)(230)(231)(232)(233)(234)(235)(236) [40,41], since holotoxin integrity is important during uptake and transport into intestinal epithelia. At the very tip of the A2 fragment, pointing toward the membrane, is a stretch of highly disordered amino acids with the KDEL-sequence (-Lys-Asp-Glu-Leu-COOH) (LT: RDEL, with Arg replacing Lys), aiding the transport of the toxin to the endoplasmic reticulum (ER) after internalization.…”
Section: A Subunitmentioning
confidence: 99%